Posted by pinki on Sunday, December 19, 2010 at 4:11pm.
prove that
d/dx 4x .√(x + √x) = 6x+5 (x)1/2/√(x + √x)
solution is
d/dx 4x.[x+(x)1/2]1/2 = d/dx 4x.[x+(x)^1/2]^1/2
d/dx 4x.[x+(x)^1/2]^1/2
Product Rule
= 4x[1/2(x+(x)^1/2)^1/2 * (1+1/2x^1/2) +[x+(x)^1/2]^1/2*4
d/dx(4 x sqrt(x+sqrt(x))) = (2 (1/(2 sqrt(x))+1) x)/sqrt(x+sqrt(x))+4 sqrt(x+sqrt(x))
am i write?

calculus  bobpursley, Sunday, December 19, 2010 at 4:43pm
I cant follow your work. Try it here. http://cs.jsu.edu/~leathrum/Mathlets/derivcalc.html